Cardiovascular Proteomics: A Post Hoc Analysis from a Phase II Randomized Clinical Trial Comparing GnRH Antagonist vs GnRH Agonist among Men with Advanced Prostate Cancer. Issue 4 (25th October 2021) - Lifshitz, Karin; Ber, Yaara; Shenhar, Chen; Nillson, Jan; Peer, Avivit; Rosenbaum, Eli; Baniel, Jack; Kedar, Daniel; Ben Zadok, Osnat Itzhaki; Margel, David
Abstract : Purpose: Recent studies demonstrated reduced cardiovascular (CV) risk with gonadotropin-releasing hormone (GnRH) antagonist, yet the underlying mechanism remains undetermined. The objective of this study was to examine longitudinal changes over time in established CV related proteins among men treated with GnRH agonists vs GnRH antagonist. Materials and Methods: We performed a proteomics analysis of serum samples collected during a phase II randomized study among 80 men with advanced prostate cancer and preexisting CV disease who were randomized to receive a GnRH agonist (39) or GnRH antagonist (41) for 1 year. Serum samples were collected at baseline and at 3, 6 and 12 months following treatment, and analyzed levels of 188 proteins using the CV panel II and III of the Olink Multiplex platform (Olink Proteomics AB, Uppsala, Sweden). We fitted a linear mixed effects model to assess evidence of a treatment effect across CV related protein values. This included terms for treatment arm, protein levels and time-by-treatment interaction. Results were corrected for multiple testing using the Benjamini-Hochberg method. Results: The CV proteomics analysis included 283 samples from 78 subjects. We identified 5 proteins with distinct patterns over time depending on study arm: human chitotriosidase, macrophage receptor with collagenous structure, cathepsin D, superoxide dismutase 2 and hydroxyacid oxidase 1. All 5 are associated with plaque stability and demonstrated an increased level among subjects in the GnRH antagonist arm compared to agonist. Conclusions: We compared longitudinal changes in CV proteins among men using androgen deprivation therapy. Our results support a direct protective effect of GnRH antagonist on plaque stability rather than a hazardous consequence of GnRH agonists on plaque rupture. This is a hypothesis generating study, and requires further confirmation.